Individualization and the Health Care Mosaic in Assisted Living. (15th June 2018) - Kemp, Candace L; Ball, Mary M; Perkins, Molly M
Abstract: Background and Objectives: Assisted living (AL) is a popular residential long-term care option for frail older adults in the United States. Most residents have multiple comorbidities and considerable health care needs, but little is known about their health care arrangements, particularly over time. Our goal is to understand how health care is managed and experienced in AL by residents and their care network members. Research Design and Methods: This grounded theory analysis focuses on the delivery of health care in AL. Qualitative data were gathered from 28 residents and 114 of their care network members followed over a 2-year period in 4 diverse settings as part of the larger study, "Convoys of Care: Developing Collaborative Care Partnerships in Assisted Living." Results: Findings show that health care in AL involves routine, acute, rehabilitative, and end-of-life care, is provided by residents, formal and informal caregivers, and occurs on- and off-site. Our conceptual model derived from grounded theory analysis, "individualizing health care, " reflects the variability found in care arrangements over time and the multiple, multilevel factors we identified related to residents and caregivers (e.g., age, health), care networks (e.g., size, composition), residences (e.g., ownership), and community and regulatory contexts. This variability leads to individualization and a mosaic of health care among AL residents and communities. Discussion and Implications: Our consideration of health care and emphasis on care networks draw attention to the importance of communication and need for collaboration within care networks as key avenues for improving care for this and other frail populations.